Annona Mucosa (Annonaceae) para o controle de pragas: estudo fitoquímico biomonitorado, síntese de mímicos e desenvolvimento de processos de nanoencapsulação - Bicalho, Keylla Utherdyany (2016)
Annona mucosa (ANNONACEAE) https://repositorio.ufscar.br/FOR PESTS CONTROL: BIOASSAY-GUIDED PHYTOCHEMICAL STUDY, SYNTHESIS OF MIMICS AND DEVELOPMENT OF NANOENCAPSULATION PROCESSES – The agriculture is one of the major drivers of Brazilian GDP. However, several losses have occurred during the agricultural productive process, especially the pest attack. Currently, leaf-cutting ants and the maize weevil have caused great economics losses and are hard to control. One alternative for these pests control is searching on nature for novel compounds with insecticide and fungicide potential. In this perspective, the first part of this work was the biassay-guided phytochemical study of Annona mucosa, searching for novel compounds with these properties. From the vegetal parts crude extracts, was verified great insecticide and fungicide potentials for its fractions. The phytochemical study of leaves and seeds crude extracts resulted on the isolation and identification of 11 secondary metabolites, 3 lignans, 4 acetogenins and 4 flavonoids, and confirmed the biological potential of these substances. Acetogenins are derived from fatty acid and are characterized by the presence of two main cores, diol-THF group and a α,β- unsaturated-γ-lactone separated by an alkyl chain. Several researches aiming the acetogenins mimics total synthesis, with simplified structures, but keeping the biologically important functionalities, have been developed. Based on this idea, the second part of this work aimed the total synthesis of rolliniastatin-1 mimics, major acetogenin on the A. mucosa chemical composition. A complete synthetic route with 12 steps was developed in order to get the polyether mimics. Although, only one complete mimic was synthesized, the synthetic rout was completely established and a new simple methodology of sequential vinyl ether exchange-Claisen Rearrangement was employed for the synthesis of γ,δ–unsaturated aldehydes. Besides, the key step, the oxidative cyclization, reaction for treo-cis-treo THF ring formation, was optimized by its yields and stereoselectivity. In the quest for developing new technologies for bioactive compounds application, the nanoencapsulaiton is a technique that results in controlled release systems of these substances and can be applied in several fields. In this way, the last part of this work was about the formulation development and improvement of process and parameters for the nanoencapsulation of the furofuranic lignan sesamin. To achieve that, a 23 factorial design was performed, where were evaluated the effect of the independent variables (type and amount of polymer and amount of oil) on the nanoparticles physical-chemistry characteristics and on the trapping, recovery and release rates. The biopolymers poly- ε-caprolactone and lignin were employed and colloidal suspensions of nanocapsules and nanospheres were prepared. The results from the factorial design proved the efficiency of both biopolymers and the best nanoformulation was the nanospheres suspension produced with 100 mg of lignina (NF3). The wide availability of lignin, which is an industrial residue, its non-toxicity to the environment and the technological application reported make this biopolymer a great potential for use in agricultural field.